Analysis Of Ethics, Sustainability and CSR In The Burger King Company - Devina Wistiasari; Teo Laiy Soon Irpan Ardiansyah; Helen Salwa; Eriva Riesquita; Esther Agustina (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
Burger King from its name alone makes you know that this company operates in the culinary sector, which is the point of its name, namely burgers, which are definitely the main menu of its name. Currently, there are many companies and individuals who sell this food, one of which is Burger King. Burger King was first founded in Miami, Florida, America. Currently, Burger King has almost 19,247 branches throughout the world and 31 branches in all cities in Indonesia. Burger King has a variety of very interesting menu variants, not only burgers but also fried chicken, potatoes, and various other menus that are no less delicious than their burgers. Burger King also makes package menus containing potatoes and drinks too, but we as consumers can also buy certain foods that we want. Burger King also often creates special menus that are only released at certain moments or collaborates with other food brands which makes it even more attractive to consumers. In Indonesia itself, Burger King has also included its company in online applications such as Gofood, Grab, and others. Burger King fans are not only adults but all groups, from children to the elderly, love this food.